2014
DOI: 10.1108/jpbm-06-2013-0324
|View full text |Cite
|
Sign up to set email alerts
|

Price presentation effects on green purchase intentions

Abstract: Purpose – This paper aims to examine the effect of price promotion presentation formats on consumers’ green purchase intentions across various levels of greenness. Despite the increasing awareness of environmental issues and green products among consumers, there is a gap between their green attitude and purchase intentions. Previous studies show that consumers’ degree of greenness varies and that price plays an important role in their green consumption decision-making. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 33 publications
4
37
0
5
Order By: Relevance
“…The findings point out that the green marketing in students of universities has a positive relationship with purchase intention, and this finding shows significant relationship between green products and green advertising with purchasing decision, and it also lined with Tang et al (2014) who showed consumer attitude positively affects purchase intention to green product. In same context demonstrates that green price has a significant positive relationship with purchase intention (Weisstein et al, 2014). Wanninayake and Randiwela (2008) stated that environment friendly products and packages make the significant impact of customer buying decisions and friendly distribution, and promotion with the environment friendly product information will also significantly impact on the buying decisions in selecting products of foods.…”
Section: Discussionmentioning
confidence: 98%
“…The findings point out that the green marketing in students of universities has a positive relationship with purchase intention, and this finding shows significant relationship between green products and green advertising with purchasing decision, and it also lined with Tang et al (2014) who showed consumer attitude positively affects purchase intention to green product. In same context demonstrates that green price has a significant positive relationship with purchase intention (Weisstein et al, 2014). Wanninayake and Randiwela (2008) stated that environment friendly products and packages make the significant impact of customer buying decisions and friendly distribution, and promotion with the environment friendly product information will also significantly impact on the buying decisions in selecting products of foods.…”
Section: Discussionmentioning
confidence: 98%
“…Word of mount affects the perceived value of goods or services. If consumers consider a product to be of high quality, they will show a higher willingness to buy it (Weisstein et al, 2014). Consumption motivation, congruity, attitudes to SNS advertising are important reasons to click ads on social media.…”
Section: Introductionmentioning
confidence: 99%
“…Consumption awareness refers to a tendency of people in showing interest on aspects related to welfare, mainly to environment, by means of their purchasing decisions and behavior (Haws et al, 2014). However, even though it involves an individual pursuit for welfare and reducing the impact of human activities on the planet (Elliott, 2013), the core of conscient purchasing decision regards to the maximization of value by consumer (Biswas & Roy, 2015;Weisstein, Asgari, & Siew, 2014).…”
Section: Awareness and Consumption: Pursuing Welfarementioning
confidence: 99%
“…On the consumption logic, it is recurrent the assumption of the individual as a resources optimizer: consumer will make a decision based on the evaluation of gains and losses incurred on the acquisition of a product (Biswas & Roy, 2015). When it comes to aware consumption the situation is not different: the purchasing decision will only be made if it adds value to the client (Weisstein et al, 2014). Although it is recognized that there is a positive attitude from many people for environment and welfare, this cannot reverberate on 'aware consumption' behaviors (Farrant et al, 2010;Luzio & Lemke, 2013).…”
Section: Aware or Convenient Consumption?mentioning
confidence: 99%
See 1 more Smart Citation